2019
DOI: 10.1093/ajae/aaz051
|View full text |Cite
|
Sign up to set email alerts
|

Eyes in the Sky, Boots on the Ground: Assessing Satellite‐ and Ground‐Based Approaches to Crop Yield Measurement and Analysis

Abstract: Understanding the determinants of agricultural productivity requires accurate measurement of crop output and yield. In smallholder production systems across low-and middle-income countries, crop yields have traditionally been assessed based on farmer-reported production and land areas in household/farm surveys, occasionally by objective crop cuts for a sub-section of a farmer's plot, and rarely using full-plot harvests. In parallel, satellite data continue to improve in terms of spatial, temporal, and spectral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(71 citation statements)
references
References 29 publications
1
70
0
Order By: Relevance
“…The correlation slightly improves to 0.40 when omitting plots with self-report values above 2500 kg/ha ( Figure 3B). The low agreement between ground-based measures is similar to that reported for maize plots in Eastern Uganda, where self-report and crop cut yields had a correlation below 0.30 even after excluding very small plots where self-reports were deemed least reliable [16]. Moving to the comparison with satellite measures, Figure 4 shows the correlation between the two ground-based yield measures and GCVI for each date of Sentinel-2 imagery, both for the raw GCVI values and the harmonic fit at those dates.…”
Section: Resultssupporting
confidence: 75%
See 3 more Smart Citations
“…The correlation slightly improves to 0.40 when omitting plots with self-report values above 2500 kg/ha ( Figure 3B). The low agreement between ground-based measures is similar to that reported for maize plots in Eastern Uganda, where self-report and crop cut yields had a correlation below 0.30 even after excluding very small plots where self-reports were deemed least reliable [16]. Moving to the comparison with satellite measures, Figure 4 shows the correlation between the two ground-based yield measures and GCVI for each date of Sentinel-2 imagery, both for the raw GCVI values and the harmonic fit at those dates.…”
Section: Resultssupporting
confidence: 75%
“…For the current study we used the Sentinel-2 Level 1-C product, which represents top-of-atmosphere reflectance. From these raw bands we calculated several common vegetation indices that have been found to be useful for agricultural monitoring in similar settings [12,15,16].…”
Section: Satellite Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work has shown that some weather variables (like temperature and water/drought) have nonlinear effects on corn yield 27,28 . There also exists another category of yield prediction using remote sensing 29 which we do not consider for this study.…”
Section: Related Workmentioning
confidence: 99%